Gambaran Nyeri Pada Pasien Kanker Payudara Post Mastektomi di RSUD Panembahan Senopati Bantul - Ni Ketut Kardiyudiani; Septiana Fathonah; Novi Widyastuti Rahayu (Jurnal Keperawatan Notokusumo, 2018)
Background: Breast cancer is a malignant tumor that begins in the breast cells. It can grow quickly and attack the surrounding tissues, or it can also spread to areas that are far from the malignant cell. Breast cancer patients often experience chronic pain conditions. The pain occurs due to the rapid and malignant growth of the disease, which changes the structure of the tissue and its functions, which finally results in pain. This study is aimed at determining the description of the pain in breast cancer patients. Method: The research design used in this study was a simple quantitative descriptive method with a cross-sectional design to determine the description of the pain in the post-mastectomy breast cancer patients. This study involved 32 respondents. Result: The results showed the characteristics of the respondents’ pain as follows: feeling being stabbed 50%, feeling hard pain 18.7%, and feeling numbness 18.7%. The degree of the pain felt by the patients was mild pain by 100%. The location of the most pain was 46.875% in the legs and 21.875 in the hands. The duration of the pain felt by the patients was > 5 minutes felt by 65.625%. Therefore, it can be concluded that the description of pain in the post-mastectomy breast cancer patients is a mild pain in the area of legs that requires further nursing intervention.